Core fucosylation and IgG function in NAIT - Aster, Richard H. (American Society of Hematology, 2014)
In this issue of Blood, Kapur et al show that maternal human platelet-specific antigen 1a (HPA 1a)-specific antibodies causing neonatal alloimmune thrombocytopenia (NAIT) possess oligosaccharides that are deficient in “core fucose” residues and appear to be more effective than fucosylated antibodies in promoting phagocytosis of antibody-coated platelets.(1)